IMMU-68. SINGLE-CELL PROTEOMIC ANALYSIS OF IMMUNE CELL RESPONSE TO CHECKPOINT BLOCKADE USING 30-PARAMETER FLOW CYTOMETRY. (5th November 2018) - Giles, Amber; Nettey, Leonard; Liechti, Thomas; Beddall, Margaret; Vera, Elizabeth; Park, Deric; Wu, Jing; Theeler, Brett; Siegel, Christine; Boris, Lisa; Garren, Nancy; Bryla, Christine; et al.
Abstract: BACKGROUND: Biomarkers of response to immunotherapy are critical to evaluate efficacy and ultimately select patients most likely to benefit from this potentially toxic treatment. Peripheral blood mononuclear cells (PBMC) are easily collected and offer abundant lymphocytes, yet the molecular determinants of cells relevant to a therapeutic response have not been determined. To identify such cells, likely rare, we developed four state-of-the-art flow cytometry assays that quantify 65 unique proteins on single-cells for comprehensive, high-throughput proteomic interrogation of PBMC and tumor-infiltrating lymphocytes. Our goal is to identify biomarkers and predictors of response to immunotherapy as well as to find potential peripheral correlates of immune responses to the tumor itself. METHODS: Molecular determinants of B, NK, DC, classical T, invariant T, NKT, and MAIT immune cell lineages and differentiation stages, as well as functional markers including cytokines, cytokine receptors, activation/senescence markers, proliferation, and markers of cytotoxicity were chosen as potential biomarkers of response. Proteomic analyses were performed on PBMC from healthy donors and patients with GBM who received checkpoint blockade therapy. RESULTS: Changes in cellular composition, cell differentiation and functional status were quantified in this comprehensive analysis of healthy donor and patient PBMC. Cellular expression patterns varied by cell activation and differentiation status; highlighting the importance of detailed subset analyses. Potential biomarkers were selected using linear discriminant analysis to identify proteomic differences between healthy donor and patient, as well as longitudinal patient PBMC samples. CONCLUSIONS: Using cutting-edge flow cytometry, we generated a comprehensive analysis of molecular and cellular changes that occur in PBMC in response to immune checkpoint blockade. Additionally, we identify sources of interpatient variation that may obscure subtle proteomic changes. This technological advance provides high-throughput proteomic analysis of live lymphocytes, which can then be sorted for downstream molecular analyses: a critical step in biomarker validation and discovery.